Characteristics of women victims of violence: an integrative review (Research, Society and Development, 2022)
Objective: to identify the characteristics of women victims of violence. Method: this is an integrative review, which used five databases, with three intersections of Health Science Descriptors in Portuguese, English and Spanish, finding a final sample of 22 articles. Results: the main characteristics were: age between 18 and 30 years old, use of alcohol/drugs, being a university student, affiliated with republics, history of neglect and child abuse, predominance of sexual violence, presence of suffering and mental disorders such as generalized anxiety disorder, depression, post-traumatic stress disorder, and schizoid, borderline, and paranoid personality disorder. Three categories of discussion emerged related to the characteristics of the victims: addictive behaviors, risk factors and behaviors, and mental disorders. Final considerations: it is evident the importance of nurses having knowledge about the factors capable of increasing the risk of violence, with the aim of working on prevention and health promotion, such as the perception of the characteristics reproduced in women victims of violence, with the objective of identifying cases early, alleviating the strong pressure caused by violence in the personal, family and social spheres, in addition to providing adequate assistance to victims.